ASUHAN KEBIDANAN IBU HAMIL DENGAN LETAK SUNGSANG PADA NY. I DI RSUD dr. DRAJAT PRAWIRANEGARA TAHUN 2019 - Halimah Tu’sadiah; Izul Zulaihah (Journal Of Applied Health Research And Development, 2019)
Breech is a location where the baby's buttocks are low with the head in the uterine fundus and the buttocks are at the bottom of the uterine cavity. The incidence of breech location in RSUD dr. Drajat Prawiranegara is 1.87%. The purpose of this study is to be able to perform midwifery care for pregnant women with breech placement in accordance with the standardization of midwifery services in the midwifery room of RSUD Dr. Drajat Prawiranegara This research uses descriptive research by using primary data through history, physical examination, ultrasound examination, and KIA books. After the assessment, it was found that NY. I had a breech and was hospitalized in the Wijaya Kusuma ward, performed by a gynecologist. Can maintain and improve quality and service in providing midwifery care for pregnant women with the breech optimally